2011
DOI: 10.1128/jvi.00825-11
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Genotype I of Japanese Encephalitis Virus as the Dominant Genotype in Asia

Abstract: Japanese encephalitis virus (JEV), a mosquito-borne zoonotic pathogen, is one of the major causes of viral encephalitis worldwide. Previous phylogenetic studies based on the envelope protein indicated that there are four genotypes, and surveillance data suggest that genotype I is gradually replacing genotype III as the dominant strain. Here we report an evolutionary analysis based on 98 full-length genome sequences of JEV, including 67 new samples isolated from humans, pigs, mosquitoes, midges. and bats in aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
157
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 32 publications
10
157
3
Order By: Relevance
“…However, the major genotype of JEV isolated in Japan changed from GIII to GI in the early 1990s (Ma et al, 2003;Yoshida et al, 2005). In recent years, a similar genotype shift has been observed in South Korea, northern Vietnam, China, Taiwan and Thailand Nam et al, 1996;Nga et al, 2004;Nitatpattana et al, 2008;Pan et al, 2011;Wang et al, 2007;Yang et al, 2004;Yun et al, 2010;Zhang et al, , 2011. GI JEV has also been found in India since 2009 (Fulmali et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…However, the major genotype of JEV isolated in Japan changed from GIII to GI in the early 1990s (Ma et al, 2003;Yoshida et al, 2005). In recent years, a similar genotype shift has been observed in South Korea, northern Vietnam, China, Taiwan and Thailand Nam et al, 1996;Nga et al, 2004;Nitatpattana et al, 2008;Pan et al, 2011;Wang et al, 2007;Yang et al, 2004;Yun et al, 2010;Zhang et al, , 2011. GI JEV has also been found in India since 2009 (Fulmali et al, 2011).…”
Section: Introductionmentioning
confidence: 78%
“…In recent years, multiple reports have indicated that GI has displaced GIII as the most frequently isolated virus genotype in a number of Asian countries, including China (8), Thailand (9), Korea (10), Japan (11), Malaysia (12), Vietnam (13), India (14), and Taiwan (15). Although two recent evolutionary studies have examined the genotype displacement of GIII by GI in China (16,17), no studies have concurrently reconstructed the spatiotemporal chronology of the emergence of GI throughout Asia and identified genetic determinants underlying the genotype displacement as it unfolded across Asia. Furthermore, even though this geographically expansive genotype displacement is suggestive of a major difference in fitness between GIII and GI viruses, the in vitro multiplication kinetics of GIII and GI viruses have never been compared in avian or mosquito cells.…”
mentioning
confidence: 99%
“…Currently, GI and GIII strains represent the most prevalent genotypes in many epidemic countries. In the first half of the 20th century, the majority of JEV isolates from humans belonged to GIII; however, over the last two decades, GI has gradually replaced GIII as the dominant circulating genotype in many areas of Asia, including China, Vietnam, Japan, India and Thailand (Ma et al, 2003;Nga et al, 2004;Nitatpattana et al, 2008;Pan et al, 2011;Parida et al, 2006;Sarkar et al, 2012). The mechanism underlying the genotype displacement as well as the impact of the genotype shift on transmission/outbreak control strategies remain largely unknown (Han et al, 2014;Schuh et al, 2013Schuh et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%